РОЛЬ СОВРЕМЕННЫХ ИНФОРМАЦИОННЫХ ТЕХНОЛОГИЙ В ОБУЧЕНИИ ИНОСТРАННОМУ ЯЗЫКУ - Омарова, Н.М. (SCIENCE and SOCIETY, 2024)
This article is devoted to how to use the Internet in the educational process. Analyzed the importance of the formation of communicative competencies in the modern educational process. Special attention is paid to the advantages of using information and communication technologies in practical English classes in universities.
Keywords: international network; communicative competence; intercultural competence; cyber space; general didactics; private method